Remoção de losartana por adsorção em biocarvão ativado das folhas da mandioca (Manihot esculenta Crantz) em meio aquoso - Gongoleski Junior , Sergio Luiz (2019)
Antihypertensive drugs, such as Losartan, have been gaining prominence among research as emerging contaminants because they have a major impact on the environment and human health. They have physical-chemical resources that make them more environmentally friendly, such as fat solubility and low biodegradability, generate poor quality water that reaches human consumption. All residue generated. Thus, this study evaluated the removal of Losartana from the aqueous environment through cassava leaf (Manihot esculenta Crantz) biochar, consumption of agroindustrial product residues, production of local products from the far west of Paraná, where production in question is related. As other regions of Brazil. A characterization of the biochar was verified by scanning electron microscopy, non-infrared electron spectroscopy, or zero charge potential, in addition to the analysis of surface groups selected by the Boehm method. A factorial experimental design was carried out using the central composite design (DCC) and the response surface methodology, with the purpose of reduction or total number of experiments to test the best adsorption condition. The factors and their levels studied were pH (4, 5 and 6), adsorbent mass (50, 100 and 150 mg) and drug concentration (78,13 mg.L-1, 156,25 mg.L-1 and 234,38 mg.L-1). They were then allowed to stir at 150 rpm for 12h at 25 °C. After filtration and reading on the spectrophotometer, calculate the final concentration and adsorbed amount of the drug. It was determined as optimum adsorption conditions and carried out or adsorption kinetics experiment. It was observed that the biochar mass did not affect drug adsorption and which the best adsorption conditions were blocked with pH and drug concentration of 4,00 and 78,13 mg.L-1, respectively. The kinetic model that best fit the pseudo-second order, with equilibrium being achieved within 360 minutes.